2020
DOI: 10.1136/rapm-2019-101027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quadratus lumborum block and caudal block for postoperative analgesia in pediatric patients undergoing inguinal hernia repair and orchiopexy surgeries: a randomized controlled trial

Abstract: Background and objectivesCaudal epidural anesthesia is a widely used popular technique for postoperative analgesia but it has potential side effects and duration of analgesia is short. Quadratus lumborum block (QLB) was found to be an effective method for postoperative analgesia in lower abdominal surgeries. In this double-blind prospective randomized trial, we aimed to compare the postoperative analgesic efficacies of QLB and the caudal block in pediatric patients undergoing inguinal hernia repair and orchiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
2
35
0
1
Order By: Relevance
“…The rate of postoperative rescue analgesia is evaluated as the number of patients who required rescue analgesia in the first postoperative 24 hours. Six trials, with 302 patients total, reported the 24 hour rescue analgesia requirement (15)(16)(17)(19)(20)(21). QL block shows a significant reduction in the rate of postoperative rescue analgesia in the first 24 hours (RR = 0.41; 95% CI = 0.28 to 0.59; P < 0.001; Fig.…”
Section: The Rate Of Postoperative Rescue Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of postoperative rescue analgesia is evaluated as the number of patients who required rescue analgesia in the first postoperative 24 hours. Six trials, with 302 patients total, reported the 24 hour rescue analgesia requirement (15)(16)(17)(19)(20)(21). QL block shows a significant reduction in the rate of postoperative rescue analgesia in the first 24 hours (RR = 0.41; 95% CI = 0.28 to 0.59; P < 0.001; Fig.…”
Section: The Rate Of Postoperative Rescue Analgesiamentioning
confidence: 99%
“…Main characteristics of the included trials. (15,16,20), 2 at 2 hours (15,20), 3 at 4 hours (15,18,20), 3 at 6 hours (15,16,20), 2 at 12 hours (15,20), and 3 at 24 hours (15,18,20). Data from the trial by Ipek (17) are not analyzed in the forest plot, as the data were presented as graphs rather than specific values.…”
Section: Postoperative Pain Scoresmentioning
confidence: 99%
“…Caudal block provides postoperative analgesia as good as TAP block, and both of them provide better analgesia than ilioinguinal/iliohypogastric block according to prospective randomized single-blinded study by Sahin et al [22] Kendall et al reached the same conclusion in their systematic review of 40 randomized controlled trials in 2018 [21]. Therefore, recently published data suggest that QLB provides significantly more effective, and longer lasting analgesia than caudal block in pediatric patients undergoing inguinal hernia repair, orchidopexy, and ureteral reimplantation [10,12,16]. Also, patients with caudal blocks have significantly longer length of hospital stay [10].…”
Section: Discussionmentioning
confidence: 97%
“…Dr. Michaela Visoiu was the first one who used it for pain management following colon surgery in pediatric patient in 2013 [5]. QLB was used as a part of a multimodal pain management technique in pediatric patients that underwent nephrectomy [6], pyeloplasty [7], orchidopexy and, inguinal hernia repair [8][9][10][11][12], hip and femur surgery [13,14], extracorporeal shock wave lithotripsy [15], and surgery for vesicoureteral reflux [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric nerve block is mostly performed under sedation or general anesthesia [21,22]. Sevo urane and propofol are currently commonly used for induction and maintenance of general anesthesia in children [23,24], but both of them have vasodilator effect.…”
Section: Discussionmentioning
confidence: 99%